Emerging Technologies in Elementary Literacy and STEAM Instruction: A Systematic Literature Review - Maarouf, Saoussan (Advances in Social Sciences Research Journal, 2025)
This systematic literature review explores the integration of emerging technologies in literacy and STEAM (Science, Technology, Engineering, Arts, and Mathematics) instruction in elementary classrooms. Drawing from twenty peer-reviewed journal articles published between 2022 and 2025, this study synthesizes trends in the use of technologies such as augmented and virtual reality (AR/VR), artificial intelligence (AI), digital storytelling, and mobile learning tools. The review identifies their impact on student engagement, literacy development, interdisciplinary learning, and digital competence. Findings highlight a growing alignment between technological innovation and constructivist pedagogy, though challenges such as teacher preparedness and equitable access remain. This review also provides a critical lens on how these technologies are positioned within broader educational systems. Recommendations are provided for educational stakeholders aiming to design effective, inclusive, technology-enhanced learning environments.